Pengaruh Perlambatan Arus Kendaraan Berdasarkan Kinerja Lalu Lintas Jalan - Ismil Nur Ramadhan; Ida Farida (Institut Teknologi Garut, 2024)
Jalan Karangpawitan is one of the roads in Garut Regency which experiences traffic jams due to the large amount of traffic from industry, schools, roadsides and community businesses that crowd the road. The aim of this research is to determine the condition of traffic flow along Jalan Karangpawitan, analyze what influences slow down vehicle flow based on traffic performance along Jalan Karangpawitan, determine the most dominant location on the influence of slow vehicle flow along Jalan Karangpawitan. The method used in this research is to use a quantitative descriptive method, direct data collection (survey), based on the 2014 Urban Road Capacity Guidelines of the Ministry of Public Works. From this research, the results obtained are the traffic flow conditions at location 1 with a degree of saturation value of 0, 96, traffic flow is unstable, sometimes vehicles stop, and the road segment is approaching capacity. Traffic flow conditions at location 2, traffic flow is unstable, speed sometimes stops, demand is approaching capacity, with a degree of saturation value of 1.27 and location 3 with a degree of saturation value of 1.28, forced traffic, low speed, low volume exceeding capacity, long queues, at location 4 with a degree of saturation value of 0.82, traffic flow is close to stable, speed can still be controlled. Traffic volume with a value of 1673.81 cur/hour, side obstacle class criteria at location 1 is low, at location 2 is very high, at location 3 is medium, at location 4 is high. For the road capacity value at location 1 it is 1526.56 cur/hour, at location 2 the road capacity value is 1282.96 cur/hour, at location 3 the road capacity value is 1494.08 cur/hour, at location 4 the road capacity value is 2378 cur/hour. The most dominant location influencing the slow flow of vehicles along Jalan Karangpawitan is location 2 or the Eyelash Factory location.